Prevalence, Genetic Diversity, and Temporary Shifts of Inducible Clindamycin Resistance Staphylococcus aureus Clones in Tehran, Iran: A Molecular–Epidemiological Analysis From 2013 to 2018 - Goudarzi, Mehdi; Kobayashi, Nobumichi; Dadashi, Masoud; Pantůček, Roman; Nasiri, Mohammad Javad; Fazeli, Maryam; Pouriran, Ramin; Goudarzi, Hossein; Miri, Mirmohammad; Amirpour, Anahita; Seyedjavadi, Sima Sadat (Frontiers in Microbiology, 2020)
The prevalence of Staphylococcus aureus as an aggressive pathogen resistant to multiple antibiotics causing nosocomial and community-acquired infections in Iran is increasing with limited therapeutic options. Macrolide-lincosamide streptogramin B (MLSB) family of antibiotics represents an important alternative therapy for Staphylococcal infections. This study was conducted within a period of five years from August 2013 to July 2018 to investigate the prevalence and molecular epidemiology of inducible resistance S. aureus. In current study, 126 inducible resistance MRSA (n=106) and MSSA (n=20) isolates were characterized by in vitro susceptibility analysis, resistance and virulence encoding gene distribution, phenotypic and genotypic analysis of biofilm formation, prophage typing, S. aureus protein A locus (spa) typing, staphylocoagulase (SC) typing, staphylococcal cassette chromosome mec (SCCmec) typing and multilocus sequence typing (MLST). Of 126 isolates, 76 (60.3%) were classified as hospital-onset (HO), 50 (39.7%) were classified as community onset (CO). Biofilm formation was observed in 97 (77%) strains. A total of 14 STs, 26 spa types, 7 coagulase types, 9 prophage types, 3 agr types (no agr IV) and 9 clonal complexes (CCs) were found in this study. The prevalence of iMLSB S. aureus increased from 7.5% (25/335) to 21.7% (38/175) during the study period. The iMLSB MRSA isolates were distributed in 9 CCs, while the MSSA isolates were less diverse, which mainly belonged to CC22 (7.95%) and CC30 (7.95%). High-level mupirocin-resistant (HLMUPR) strains belonged to ST85-SCCmec IV/t008 (n=4), ST5- SCCmec IV/t002 (n=4), ST239-SCCmec III/t631 (n=2), ST8-SCCmec IV/t064 (n=2) clones, while low-level mupirocin-resistant (LLMUPR) strains belonged to ST15-SCCmec IV/t084 (n=5), ST239-SCCmec III/t860 (n=3), ST22-SCCmec IV/t790 (n=3) clones. All the fusidic acid resistant iMLSB isolates were MRSA and belonged to ST15-SCCmec IV/t084 (n=2), ST239- SCCmec III/t030 (n=2), ST1-SCCmec V/t6811 (n=1), ST80-SCCmec IV/t044 (n=1), and ST59-SCCmec IV/t437 (n=1). The CC22 that was predominant in 2013-2014 (36% of the isolates) had almost disappeared in 2017-2018, being replaced by the CC8, which represented 39.5% of the 2017–2018 isolates. This is the first description of changing molecular epidemiology and temporal shifts of iMLSB S. aureus isolates in Iran that identify predominant clones and treatment options of iMLSB S. aureus related infections.